THE UNDERCLASS IN THE WORKS OF CHARLES DICKENS AND ITS MARXIST THEMES - Kukuh Prayitno Subagyo (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
In his novels, Dickens delivers important social messages through his empathetic characters living lives of misery, oppression, slavery, degradation, and exploitation under the so-called capitalistic system. These underclass people hollertheir plight of injustice and crises of the actual social milieu. In the Marxist perspective, these multiple crises are embedded in themes of exploitation, class consciousness, and sacrifice and revolution. Hence, the realism disguised under literary devices could hopefully accomplish dual purposes, both as a means of provoking a new kind of "social consciousness" among the bourgeoisie and as ameans of raising the proletariat's class consciousness